Parallel programming - Schmidt, Bertil; Gonzalez-Dominguez, Jorge; Hundt, Christian; Schlarb, Moritz (USA Morgan Kaufmann, 2018)
Parallel Programming: Concepts and Practice provides an upper level introduction to parallel programming. In addition to covering general parallelism concepts, this text teaches practical programming skills for both shared memory and distributed memory architectures. The authors' open-source system for automated code evaluation provides easy access to parallel computing resources, making the book particularly suitable for classroom settings.
Keywords: Parallel programming (Computer science); Parallel programming (Computer science)